Immunogenicity of the Currently Recommended Pneumococcal Vaccination Schedule in Patients With Inflammatory Bowel Disease. (22nd March 2019) - van Aalst, Mariëlle; Garcia Garrido, Hannah M; van der Leun, Josephine; Meek, Bob; van Leeuwen, Ester M M; Löwenberg, Mark; D'Haens, Geert R; Ponsioen, Cyriel Y I; Grobusch, Martin P; Goorhuis, Abraham
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at increased risk of invasive pneumococcal infections. Therefore, vaccination with the 13-valent pneumococcal conjugate vaccine (PCV13) followed by 23-valent pneumococcal polysaccharide vaccine (PPSV23) 2 months later is recommended. However, the level of immunogenicity induced by this vaccination schedule in IBD patients with and without immunosuppressive medication remains unclear. Methods: We prospectively assessed the immunogenicity of PCV13 followed by PPSV23 in IBD patients by measuring serotype-specific pneumococcal immunoglobulin G antibody concentrations at baseline and 4–8 weeks postvaccination. Response to vaccination was defined as a postvaccination antibody concentration ≥1.3 μg/mL for 70% of the measured serotypes. We analyzed the immunogenic effect of 4 different medication regimens: (1) conventional immunomodulators (ie, oral prednisolone >10 mg/day, thiopurines, methotrexate); (2) anti–tumor necrosis factor agents; (3) combination therapy; and (4) no treatment with immunosuppressive agents (control group). Results: One hundred forty-one IBD patients were included, of whom 37 were controls. Adequate response to vaccination was 59% (61/104) in patients using immunosuppressive agents (groups 1–3) vs 81% (30/37) in controls (odds ratio, 0.33 [95% confidence interval, .13–.82]). A combination of different immunosuppressive drugs most severely impaired the immune response to pneumococcal vaccination (response, 52% [15/29]). Conclusions: Although the sequential vaccination schedule of PCV13 followed by PPSV23 is safe, immunogenic, and thus beneficial in the majority of IBD patients, those receiving immunosuppressive agents, and especially those receiving combination therapy, have an impaired immune response compared to controls. Therefore, preferably, vaccinations should be administered before the initiation of immunosuppressive therapy. Clinical Trials Registration: Dutch trial register #6315. Abstract : Vaccination with 13-valent pneumococcal conjugate vaccine followed by 23-valent pneumococcal polysaccharide vaccine is safe and immunogenic in patients with inflammatory bowel disease. However, those receiving immunosuppressive agents have an impaired response to vaccination. Therefore, pneumococcal vaccines should be administered before the start of immunosuppressive therapy.